A descriptive study on “Istana Besar” design of architecture as an iconic building in Johor / Shahril Amri Samsul Kamal - Samsul Kamal, Shahril Amri (2019)
This research provides a document of the historical architecture design on “Istana Besar” in Johor and preserve the architecture design as an iconic building. The use of document and preserve in this study to encourage the public to know about the existence of a historic building. The purpose of this study is to gain information about what people need to attract them to know the building. The method used in this study is qualitative research using formalistic concept. As a field of study, qualitative approaches include research concepts and from multiple established academic fields. Whereby an interview have been conduct at selected area. This analysis shows that the Palace has various important events throughout the building was constructed. In addition, there is also a color transition and the shape of the Great Palace of the new Sultan's government. The results of the study revealed the improved of documenting and preserving an iconic building to make sure the other generations get inform about the building. The outcome of this study is to tell people why that building are more important to be document and preserve, beside it will lead to promoted tourist come to visit Johor and Malaysia